Obedient rebellion: nuclear-weapon-free zones and global nuclear order, 1967–2017 - Mpofu-Walsh, S (2020)
Nuclear-weapon-free zones (NWFZs) cover territories from Africa to Latin America, and from the South Pacific to Southeast Asia. Yet traditional and critical scholars alike under-value their importance to global nuclear order and International Relations theory. In a comparative case study of the African, Latin American, and South Pacific NWFZs, I draw on archival and oral historical evidence to analyse why these zones exist, and why they persist. All three zones were triggered, I assert, by external nuclear interventions into already-peaceful, postcolonial contexts. The zones exist and persist, I contend, by paradoxically symbolising both obedience to—and rebellion against— global nuclear order. To actors inside the zones, on one hand, they legitimise an institutionally unequal nuclear order; on the other, they echo a tradition of postcolonial anti-nuclear solidarity. To the nuclear-weapon states, NWFZs at once tokenise nuclear responsibility, and entrench nuclear hierarchy. Counterintuitively, these ambivalences consolidate these zones by accommodating multiple, conflicting domestic and international audiences simultaneously. NWFZs thus offer unique insight into the complex, contending forces that balance nuclear order.